Two scandium coordination polymers: rapid synthesis and catalytic properties. Issue 35 (31st July 2019) - Zhu, Ziqian; Tao, Yufang; Jiang, Yansong; Zhang, Liying; Xu, Jianing; Wang, Li; Fan, Yong
Abstract : Two new scandium coordination polymers were synthesized by MW and hydrothermal methods, and exhibited good catalytic performance. Abstract : Two scandium coordination polymers (Sc-CPs), [Sc(L 1 )2 (DMF)] (DMF = N, N ′-dimethyl formamide, H2 L 1 = pyrazine-2, 3-dicarboxylic acid) (1 ) and [Sc(L 2 )(C2 O4 )0.5 (H2 O)2 ]·H2 O (H2 L 2 = pyrazine-2, 5-dicarboxylic acid) (2 ), were prepared via hydrothermal and microwave (MW) heating techniques. It is noted that MW heating can effectively accelerate the reaction compared with a conventional hydrothermal method and decrease the crystal size of the samples.1 shows a 1D non-planar double chain, while2 exhibits a brick-like 2D network. After activation, 1 and2 exhibit good catalytic performance for the cyanosilylation reaction of aromatic aldehydes; in addition, the catalysts prepared by the MW method exhibit better catalytic activity compared with those synthesized by the conventional hydrothermal method.